Preparing for adolescence : how to survive the coming years of change : Growth guide - Dobson, James C., 1936- (Ventura, Calif., U.S.A. : Regal Books, 2000)
Speaks to adolescents about such topics as drug abuse, sex, family conflict, friendship, love, and conformity.
Keywords: Adolescence -- Juvenile literature; Teenagers -- Conduct of life; Teenagers -- Religious life; Conduct of life; Christian life